missing oocyte encodes a highly conserved nuclear protein required for the maintenance of the meiotic cycle and oocyte identity in Drosophila. - Iida, T.; Lilly, M.A. (Development, 2004)
In Drosophila, a single oocyte develops within a 16-cell germline cyst. Although all 16 cells initiate meiosis and undergo premeiotic S phase, only the oocyte retains its meiotic chromosome configuration and remains in the meiotic cycle. The other 15 cells in the cyst enter the endocycle and develop as polyploid nurse cells. A longstanding goal in the field has been to identify factors that are concentrated or activated in the oocyte, that promote meiotic progression and/or the establishment of the oocyte identity. We present the characterization of the missing oocyte gene, an excellent candidate for a gene directly involved in the differentiation of the oocyte nucleus. The missing oocyte gene encodes a highly conserved protein that preferentially accumulates in pro-oocyte nuclei in early prophase of meiosis I. In missing oocyte mutants, the oocyte enters the endocycle and develops as a polyploid nurse cell. Genetic interaction studies indicate that missing oocyte influences meiotic progression prior to pachytene and may interact with pathways that control DNA metabolism. Our data strongly suggest that the product of the missing oocyte gene acts in the oocyte nucleus to facilitate the execution of the unique cell cycle and developmental programs that produce the mature haploid gamete.